Kebudayaan Bali Dan Agama Hindu - I Ketut Wartayasa (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
Bali has its own distinctive cultural diversity in which Hindu religion is its soul. The religion, customs and culture of Bali is an inseparable unity. The growing Hindu religion in Bali harmonizes with a local religion rich in customs and culture. The Hindu presence in Bali embraces the local religion. The arrival of Hinduism in Bali from both India and Java is accepted selectively and adaptively in the presence of religion and local communities. Balinese Hinduism already has an identity, a character different from India but essentially the same. In culture, Hinduism flourishes because it provides a religiously humanist space so that Hindu religion is flexible and universal.